Pengaruh Aromatic Footbath Hydrotherapy Terhadap Penurunan Tingkat Depresi Pada Lansia di Gamping, Sleman - Hidayati, Rizqi Wahyu; Fadilla, Febby (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Jenderal Achmad Yani Yogyakarta, 2025)
Background: Depression is a mental disorder that is often experienced by the elderly as a result of physical, psychological, and social changes. In the elderly, depression can reduce quality of life and cause emotional distress. One of the efforts to manage depression in the elderly with aromatic footbath hydrotherapy. Objective: This study aims to determine the effect of aromatic footbath hydrotherapy on elderly depression in Gamping. Methods: This study used a quasy-experiment design with pre and post-test control group design. Purposive Sampling of 60 respondents was taken in the study. The inclusion criteria were ≥ 55 years old and they had one or more depression symptoms; the exclusion criteria were dementia and diabetic ulcer. The depression instrument was the Geriatric Depression Scale (GDS-15). Statistical analysis was performed with Wilcoxon Test and Mann-Whitney Test. This study was conducted every day for 3 weeks, with a duration of 15 minutes each section of therapy. Results: Depression in the elderly at pretest in the intervention group had an mean ± SD (4.57 ± 2.128) and in the control group the mean ± SD was (2.90 ± 1.647). While during the posttest, in the intervention group had an mean ± SD (2.87 ± 1.279) and the control group dropped into (2.60 ± 1.354). Based on the Wilcoxon test, it had p: 0.000 (p<0.05), indicated the therapy was effective for decreasing depression on elder adults. Conclusion: The aromatic footbath hydrotherapy therapy was effective for decreasing depression on the elderlys’ in Gamping. For further research, the researcher should control constantly the water’s temperature (390C ).